Short Communication: Fish fauna of Lake Lauik Tawar and Lake Laulo, Simeulue Island, Indonesia - ZAINAL A. MUCHLISIN; NURFADILLAH NURFADILLAH; IKO IMELDA ARISA; ALVI RAHMAH; DEDI F. PUTRA; MUHAMMAD NAZIR; ARMEN ZULHAM (Society for Indonesian Biodiversity, 2017)
Muchlisin ZA, Nurfadillah N, Arisa II, Rahmah A, Putra DF, Nazir M, Zulham A. 2017. Short Communication: Fish fauna of Lake Lauik Tawar and Lake Laulo, Simeulue Island, Indonesia. Biodiversitas 18: 752-757. The objectives of the present study were to evaluate the species composition and diversity index of fishes in Lake Lauik Tawar and Lake Laulo, Simeulue Island, Aceh Province, Indonesia. The survey was conducted from 17th to 21st of November 2015. The fishes were sampled using gillnets with mesh size 1-3 inches. The representative of each species was photographed and then preserved in 10% formalin and transported for taxonomic identification in the Laboratory of Ichthyology, Syiah Kuala University, Banda Aceh, Indonesia. The study showed that there were 11 species of fish recorded during the survey; where eight species were found in Lake Lauik Tawar and six species were found in Lake Laulo. Two species of alien fish were recorded in Lake Lauik Tawar, i.e. Osphronemus gouramy and Oreochromis niloticus and one species in Lake Laulo i.e. O. niloticus. In addition, Ambassis miops and Clarias batrachus were predominant species in Lake Lauik Tawar and Lake Laulo, respectively. In general, the two lakes were categorized as a low degree of fish diversity.